Pengaruh Quality Product, Celebrity Endorsement, Dan Brand Image Terhadap Keputusan Pembelian (Studi Kasus Pada Pengguna Produk MS Glow Kota Malang) - Novi Faradila; Mohammad Rizal; Tri Sugiarti Ramadhan (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of Product Quality, Celebrity Endorsement, and Brand Image on Purchasing Decisions (Case Study on MS Glow users in Malang City). The population in this study were MS Glow users in Malang City. The sampling method used a non-probability sampling technique to determine the sample based on chance by using a questionnaire distributed to obtain 75 respondents, using SPSS. The results of this study partially conclude that the variables Quality Product, Celebrity Endorsement and Brand Image have a significant influence on purchasing decisions and simultaneously conclude that there is a significant influence between the variables Product Quality, Celebrity Endorsement and Brand Image on purchasing decisions. Keywords: Quality Product, Celebrity Endorsement, and Brand Image on Purchasing Decision.